Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/mnras/staa2162
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty principle for star formation – V. The influence of dust extinction on star formation rate tracer lifetimes and the inferred molecular cloud lifecycle

Abstract: Recent observational studies aiming to quantify the molecular cloud lifecycle require the use of known “reference time-scales” to turn the relative durations of different phases of the star formation process into absolute time-scales. We previously constrained the characteristic emission time-scales of different star formation rate (SFR) tracers, as a function of the SFR surface density and metallicity. However, we omitted the effects of dust extinction. Here, we extend our suite of SFR tracer emission time-sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We refer the reader to Kruijssen & Longmore (2014) for a detailed explanation of the method, to Kruijssen et al (2018) for the presentation and validation of the HEISENBERG code, as well as the full list of input parameters, and to Chevance et al (2020c) for a general application of the method to nine nearby starforming galaxies. The accuracy of the method has been demonstrated in Kruijssen et al (2018) using simulated galaxies, and has since been confirmed through extensive observational and numerical testing (Kruijssen et al 2019;Haydon et al 2020a;Ward et al 2020b).…”
Section: E T H O Dmentioning
confidence: 82%
See 1 more Smart Citation
“…We refer the reader to Kruijssen & Longmore (2014) for a detailed explanation of the method, to Kruijssen et al (2018) for the presentation and validation of the HEISENBERG code, as well as the full list of input parameters, and to Chevance et al (2020c) for a general application of the method to nine nearby starforming galaxies. The accuracy of the method has been demonstrated in Kruijssen et al (2018) using simulated galaxies, and has since been confirmed through extensive observational and numerical testing (Kruijssen et al 2019;Haydon et al 2020a;Ward et al 2020b).…”
Section: E T H O Dmentioning
confidence: 82%
“…The absolute duration of the different phases is then obtained by scaling the relative duration of timescales with a reference time-scale (t ref ). In our previous analyses using CO and H α observations (Kruijssen et al 2019;Chevance et al 2020c, a;Hygate 2020;Ward et al 2020a), we used the duration of the isolated H α emitting phase (t ref = t H α − t fb, H α ), calibrated by Haydon et al (2020b), Haydon et al (2020a) using the stellar population synthesis model SLUG2 (da Silva, Fumagalli & Krumholz 2012Krumholz , 2014Krumholz et al 2015), as the reference timescale. Here, in order to obtain absolute values when applying our analysis to CO and 24 μm maps, we first apply the method to CO and H α observations.…”
Section: Description Of the Analysis Methodsmentioning
confidence: 99%
“…3). Haydon et al (2020a) revisited results from Haydon et al (2020b) by quantify the impact of dust extinction, find that extinction mostly decreases the SFR tracer emission timescale (factor of a few for H𝛼). Observationally, correlating maps of different light tracers such as H𝛼, CO and 24𝜇m on spatially resolved scales to empirically constrain the giant molecular cloud lifecycle (see also Kruijssen et al 2019;Chevance et al 2020), Kim et al (2021) found a duration of H𝛼 emitting phase of 5.5-8.9 Myr for nearby spiral galaxies, which is consistent with our dust-corrected timescale estimates.…”
Section: Timescale Of the Hα Sfr Tracermentioning
confidence: 99%
“…We note that the choice of the CO-to-H 2 conversion factor does not affect the time-scales determined here, unless there are considerable variations within the galaxy on the scale of independent regions (a few 100 pc; see also discussion inKruijssen et al 2018;Chevance et al 2020b). In addition, in the galaxies of our sample, ranging from solar to half-solar metallicity, we do not expect high-mass star formation to take place in completely CO-dark clouds, which would require a different calibration of the timeline(Haydon et al 2020a). …”
mentioning
confidence: 91%
“…Kruijssen et al 2019;Chevance et al 2020b;Hygate 2020;Ward et al 2020;Zabel et al 2020) and are dispersed within a few Myr after the onset of high-mass star formation, as visible in H𝛼 emission (e.g. Whitmore et al 2014;Hollyhead et al 2015;Grasha et al 2018Grasha et al , 2019Hannon et al 2019;Chevance et al 2020b,a;Haydon et al 2020a). It is an open question which physical mechanisms drive GMC dispersal.…”
Section: Introductionmentioning
confidence: 99%